Cerebral Immunohistochemical Characterization of the H2S and the Oxytocin Systems in a Porcine Model of Acute Subdural Hematoma - Denoix, Nicole; Merz, Tamara; Unmuth, Sarah; Hoffmann, Andrea; Nespoli, Ester; Scheuerle, Angelika; Huber-Lang, Markus; Gündel, Harald; Waller, Christiane; Radermacher, Peter; McCook, Oscar (Frontiers in Neurology, 2020)
The hydrogen sulfide (H2S) and the oxytocin/oxytocin receptor (OT/OTR) systems interact in trauma and are implicated in vascular protection and regulation of fluid homeostasis. Acute brain injury is associated with pressure-induced edema formation, blood brain barrier disruption and neuro-inflammation. The similarities in brain anatomy: size, gyrencephalic organization, skull structure, may render the pig a highly relevant model for translational medicine. Cerebral biomarkers for pigs for pathophysiological changes and neuro-inflammation are limited. The current study aims to characterize the localization of OT/OTR and the endogenous H2S producing enzymes together with relevant neuro-inflammatory markers on available porcine brain tissue from an acute subdural hematoma (ASDH) model. In a recent pilot study, anesthetized pigs underwent ASDH by injection of 20 mL of autologous blood above the left parietal cortex and were resuscitated with neuro-intensive care measures. After 54 h of intensive care, the animals were sacrificed, the brain was removed and analyzed via immunohistochemistry. The endogenous H2S producing enzymes cystathionine-ɣ-lyase (CSE) and cystathionine-β-synthase (CBS), the OTR, and OT were localized in neurons, vasculature and parenchyma at the base of sulci, where pressure-induced injury leads to maximal stress in the gyrencephalic brain. The pathophysiological changes in response to brain injury in humans and pigs, we show here, are comparable. We additionally identified modulators of brain injury to further characterize the pathophysiology of ASDH and which may indicate future therapeutic approaches.